PEMBUATAN MINIATUR RUMAH ADAT PAPUA DENGAN MEMANFAATKAN LIMBAH DAUR ULANG - Bindamar Kastela; Adi Rahmadi; Diana Ulfah (Jurnal Sylva Scienteae, 2021)
The purpose of this research is to develop creativity in making Minatur Papuan traditional houses (Honai and Kariwari) and to analyze economically if these products are made into the home industry. The materials used in making miniature traditional houses mostly come from the surrounding environment and the costs incurred for making them are cheap. These materials include bamboo, used plywood, used biscuit cans, dried banana leaves, galam tree bark and grass grass. The tools used also have a relatively long service life depending on the quality of the goods and the cost of shrinkage is small. The difference between these two miniatures can be seen in the pictures of each of these miniature houses. This miniature honai is round, the roof is conical. This honai house is located in the Beliem valley. Kariwari is the home of the repentance tribe located on the coast of Yotefa Bay and Lake Sentani Jayapura. This Kariwari house is in the form of an octagonal linmas, the Kariwari traditional house is above sea water. Kariwari houses are for both men and women. The traditional house of the tobati tribe Kariwari is one of the houses that has become the symbol of the Persipura Jayapura logo. Utilization of the waste cycle can be marketed by creating the value of an item that was not previously valuable into a valuable item. The development of creativity in making miniature Papuan traditional houses (honai and Kariwari) will increase people's income if these products are made into home industries.Keywords: Papua; Traditional House; Waste